2001
DOI: 10.1046/j.1365-2567.2001.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of interferon‐γ in neonatal SOCS1−/− mice prevents fatty degeneration of the liver but not subsequent fatal inflammatory disease

Abstract: SUMMARYMice lacking the suppressor of cytokine signalling-1 (SOCS1) die within weeks of birth with extensive fatty degeneration of the liver, consistent with acute hepatic toxicity to interferon-c (IFN-c), and in¯ammation of multiple organs. We show here that treatment for 1 week from birth with neutralizing antibody to IFN-c rescues SOCS1x/x mice from lethal liver disease but the mice subsequently succumb to chronic in¯ammatory lesions characterized by T-lymphocyte in®l-tration of skeletal muscle, pancreas, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…Previous studies have shown that T cells from SOCS-1 Ϫ/Ϫ mice display features of activated T cells, such as an increase in cell size and expression of the activation markers CD44, CD69, and CD25 (17,28,29). These features were also typical of T cells from SOCS-1 Ϫ/Ϫ IFN-␥ Ϫ/Ϫ mice.…”
Section: T Cell Activation In Socs-1 ϫ/ϫ Mice Occurs In the Absence Omentioning
confidence: 74%
“…Previous studies have shown that T cells from SOCS-1 Ϫ/Ϫ mice display features of activated T cells, such as an increase in cell size and expression of the activation markers CD44, CD69, and CD25 (17,28,29). These features were also typical of T cells from SOCS-1 Ϫ/Ϫ IFN-␥ Ϫ/Ϫ mice.…”
Section: T Cell Activation In Socs-1 ϫ/ϫ Mice Occurs In the Absence Omentioning
confidence: 74%
“…It suggested that the hypersensitivity of the mice to IFN-γ caused that inflammatory syndrome. SOCS-1 was a key negative regulator of gamma interferon action in vivo [29] and can inhibited the extent of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies support the concept that the protective effect of SAMe and PTCA (GSH prodrugs) are mediated by prompting the biosynthesis of hepatic GSH. Finally orally administered SAMe [20] as well as PTCA [33] have been reported to be well tolerated and safe.…”
Section: Discussionmentioning
confidence: 99%